Cover Feature: Pyrrolidine‐Based P, O Ligands from Carbohydrates: Easily Accessible and Modular Ligands for the Ir‐Catalyzed Asymmetric Hydrogenation of Minimally Functionalized Olefins (ChemCatChem 23/2018). Issue 23 (7th December 2018) - Elías‐Rodríguez, Pilar; Borràs, Carlota; Carmona, Ana T.; Faiges, Jorge; Robina, Inmaculada; Pàmies, Oscar; Diéguez, Montserrat
Abstract : The Cover Feature shows carbohydrates as precursors for the synthesis of new Ir/P, O‐iminosugar based catalysts for the asymmetric hydrogenation of minimally functionalized olefins. In their Full Paper, P. Elías‐Rodríguez et al. demonstrate that, in comparison to related proline‐based P, O ligands, the use of a more rigid bicyclic backbone increases enantioselectivity and expands the scope of the reaction to include 1, 1‐disubstituted allylic acetates. The diphenyl phosphine moiety in the iminosugar ligand improves stability, relative to that of proline‐based P, O ligands containing bulkier phosphine groups. More information can be found in the Full Paper by P. Elías‐Rodríguez et al. onpage 5414 in Issue 23, 2018 (DOI:10.1002/cctc.201801485 ).